2012
DOI: 10.1001/archgenpsychiatry.2011.1893
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Apolipoprotein E Genotype and Age on Hippocampal Activation During Memory Processing in Healthy Adults

Abstract: The findings support the hypothesis that aging and APOE allele status have interacting effects on the neural substrate of episodic memory and lend clarification to disparities in the literature. The stepwise decrease in activation with age found among genotype groups resembles the order of susceptibility to Alzheimer disease, suggesting a compensatory neurobiological mechanism in older asymptomatic ϵ4 carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 74 publications
2
23
1
Order By: Relevance
“…gray-matter volumes. However, data from another lifespan fMRI study suggested an opposite pattern for hippocampal activation in older adults [27]. In this study there was decreased hippocampal activity during encoding and retrieval of neutral pictures with increasing age, and these decreases were weaker for e4 carriers than for non-carriers.…”
Section: Low Highcontrasting
confidence: 61%
See 1 more Smart Citation
“…gray-matter volumes. However, data from another lifespan fMRI study suggested an opposite pattern for hippocampal activation in older adults [27]. In this study there was decreased hippocampal activity during encoding and retrieval of neutral pictures with increasing age, and these decreases were weaker for e4 carriers than for non-carriers.…”
Section: Low Highcontrasting
confidence: 61%
“…In line with this notion, participants were instructed to remember images in the study where older e4 carriers had lower brain activity at encoding [26]. This task is clearly more cognitively challenging than judging the contents of images during study, a task for which greater brain activity in older e4 carriers was observed [27]. Concerning structural brain-imaging markers, longitudinal studies demonstrate more hippocampal atrophy for e4 carriers [29,30] that may contribute to the effects of APOE on functional brain activity.…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
“…AD targets specific neural networks that have high metabolic demand, and areas within those networks that function as 'connectivity hubs' with other brain regions are particularly at risk, including the posterior cingulate and precuneous, the medial frontal cortex, and the lateral frontal and parietal regions [46,47]. It is intriguing that in functional imaging studies of older adults with normal cognition, these same regions show evidence of initial hyper-metabolism and increased neuronal activity as well as increased Ab deposition [48][49][50][51]. This increased activity is associated with preservation of brain function, suggesting it serves as a compensatory response.…”
Section: Energetics Neural Network and Alzheimer's Diseasementioning
confidence: 99%
“…AD-related regional brain functional and structural impairments included a decreased volume of the medial temporal lobe (MTL; Geroldi et al, 1999;Hashimoto et al, 2001), lower cerebral metabolic rates (Reiman et al, 1996), greater whole brain atrophy rates (Chen et al, 2007), and disrupted anterior and posterior WM regions (Nierenberg et al, 2005;Persson et al, 2006;Ryan et al, 2011). It was also reported that behavior/performance or cholesterol levels were associated with certain functional (Nichols et al, 2012) and structural (Ryan et al, 2011) brain damage and with glucose hypometabolism in cognitively normal individuals in an APOE e4 status dependent fashion (Reiman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%